Rancang Bangun Sistem Anjungan Layanan Mandiri Pencetakan Dokumen - Alri, Hamid; Sambul, Alwin M.; Sompie, Sherwin R.U.A (Jurnal Teknik Informatika, 2021)
Document printing self-service platform is a printing machine that uses a computerized system to serve and assist users in printing documents, for example for the needs of legalizing academic documents such as diplomas needed by alumni who want to find work or continue their education to a higher level as evidence and complementary documents. However, the process of managing document legalization is still done manually. alumni come with a copy of the document and bring proof of payment then submit it to the officer in charge of legalizing the document in the validation process and doing data collection manually. This allows the legalization process activities to not be carried out properly which results in documents being scattered or lost and there is no certainty that the document legalization process will be completed.Â The research entitled "Design of a Document Printing Automated Automated Service Platform" aims to eliminate some of the shortcomings of the manual Legalization process. This research designs a machine that can receive digitally copied documents and print legalized documents in an abstract way. This machine has a computer in which there is a Website application and has been connected to a document printer. This application will ask the user to upload documents in digital form according to the user's request. Later, when the user completes the requirements, this application can print the document. the sheet of paper contained in the printing press has previously been affixed with a stamp and signature, thus issuing a legalized copy of the document. It is hoped that with this machine, various problems related to legalization can be minimized and made more effective and efficientAnjungan Layanan mandiri pencetakan dokumen merupakan sebuah mesin cetak yang telah menggunakan sistem komputerisasi untuk melayani dan membantu pengguna melakukan pencetakan dokumen, misalnya untuk kebutuhan Legalisir dokumen akademik seperti ijazah dibutuhkan alumni yang ingin mencari pekerjaan atau melanjutkan Pendidikan ke jenjang yang lebih tinggi sebagai bukti dan pelengkap dokumen. Namun proses pengelolahan legalisir dokumen masih dilakukan secara manual yaitu alumni datang membawa dokumen salinan dan membawa bukti pembayaran kemudian menyerahkan kepada petugas penanggung jawab legalisir dokumen dalam proses pengesahaan dan melakukan pendataan secara manual. Hal itu memungkinkan kegiatan proses legalisir tidak bisa dilakukan dengan baik yang mengakibatkan dokumen bisa saja tercecer atau hilang dan tidak ada kepastian terselesainya proses legalisir dokumen.Penelitian dengan judul â€œRancang Bangun Sistem Anjungan Layanan Mandiri Pencetakan Dokumenâ€ bertujuan untuk menghilangkan beberapa kekurangan dari proses Legalisir secara manual. Penelitian ini merancang sebuah mesin yang dapat menerima dokumen Salinan secara digital dan mencetak dokumen terlegalisir secara abstrak. Mesin ini terdapat sebuah komputer didalamnya terdapat sebuah aplikasi Website dan telah terhubung dengan pencetak dokumen. aplikasi ini akan meminta pengguna untuk mengupload dokumen dalam bentuk digital sesuai permohonan pengguna. Nantinya pada saat pengguna menyelesaikan persyaratan, aplikasi ini dapat mencetak dokumen. lembar kertas yang terdapat pada mesin cetak tersebut sebelumnya telah dibubuhi stampel dan tanda tangan, sehingga mengeluarkan dokumen Salinan yang terlegalisir. Diharapkan dengan adanya mesin ini, berbagai permasalahan terkait legalisir dapat diminimalisir dan di buat menjadi lebih efektif dan effisien